(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
Coalition government, is a body of advisors that is formed when different political parties choose to cooperate in the administration and regulation of a country or community. The paper deal with the creation of coalition government in India. The paper discussed about how coalition government leads to the multi-party democracy in India since 1967-2009.One of the main advantages of a coalition government is that due to having to share a mandate, this leads to broader representation, as the two or more parties have to compromise on their opposing ideologies in order to create policies that result in legislation.